(untitled) (Medical Forum Monthly, 2020)
Objective: Stroke is extremely common in our set up, it is associated with high risk of mortality, morbidity and permanent disability but very little is known about it by the general public in a developing country like Pakistan. So the main objective of the study was to find out the clinical presentation and the risk factors associated with acute ischemic stroke and to know about the general public awareness about stroke. Study Design: Descriptive /cross-sectional study Place and Duration of Study: This study was conducted at the Medical Units of Mardan Medical Complex (M.M.C), Mardan from July 2019 to December 2019. Materials and Methods: Adult 183 male and female patients of acute ischemic stroke admitted through emergency and medical OPD in medical units of MMC were included in study after taking an informed verbal consent from them. Following detailed history and clinical examination they were subjected to relevant investigations and CT brain. Patients with finding of bleed on CT and those having venous infarct were excluded. Results: Hyperlipidemias, hypertension, diabetes and smoking were the major risk factors causing ischemic stroke in our sample of patients. Other risk factors given in detail below were also present, atrial fibrillation was found to be common risk factor in elderly population. 24% of patients presented with re stroke. Conclusion: It was concluded that majority of patients were unaware of the risk factors causing stroke, so if we as a professional not only treat them but also educate them the incidence of stroke can be considerably reduced in society.